An In Vitro and In Silico Perspective Study of Seed Priming with Zinc on the Phytotoxicity and Accumulation Pattern of Arsenic in Rice Seedlings - Shuvasish Choudhury; Debojyoti Moulick; Muhammed Khairujjaman Mazumder; Binaya Kumar Pattnaik; Dibakar Ghosh; Lakshminarayana R. Vemireddy; Adil Aldhahrani; Mohamed Mohamed Soliman; Ahmed Gaber; Akbar Hossain (MDPI AG, 2022)
Arsenic (As) contamination of the rice agro-ecosystem is a major concern for rice farmers of South East Asia as it imposes a serious threat to human and animal life; thus, there is an unrelenting need to explore the ways by which arsenic stress mitigation could be achieved. In the present investigation, we explore the effect of zinc (Zn2+) supplementation using the seed priming technique for the mitigation of As-induced stress responses in developing rice seedlings. In addition to the physiological and biochemical attributes, we also studied the interactive effect of Zn2+ in regulating As-induced changes by targeting antioxidant enzymes using a computational approach. Our findings suggest that Zn2+ and As can effectively modulate redox homeostasis by limiting ROS production and thereby confer protection against oxidative stress. The results also show that As had a significant impact on seedling growth, which was restored by Zn2+ and also minimized the As uptake. A remarkable outcome of the present investigation is that the varietal difference was significant in determining the efficacy of the Zn2+ priming. Further, based on the findings of computational studies, we observed differences in the surface overlap of the antioxidant target enzymes of rice, indicating that the Zn2+ might have foiled the interaction of As with the enzymes. This is undoubtedly a fascinating approach that interprets the mode of action of the antioxidative enzymes under the metal/metalloid-tempted stress condition in rice by pointing at designated targets. The results of the current investigation are rationally significant and may be the pioneering beginning of an exciting and useful method of integrating physiological and biochemical analysis together with a computational modelling approach for evaluating the stress modulating effects of Zn2+ seed priming on As-induced responses in developing rice seedlings.